Juvenile-onset PSAT1-related neuropathy: A milder phenotype of serine deficiency disorder - Shen, Yu; Peng, Yun; Huang, Pengcheng; Zheng, Yilei; Li, Shumeng; Jiang, Kaiyan; Zhou, Meihong; Deng, Jianwen; Zhu, Min; Hong, Daojun (Frontiers in Genetics, 2022)
Background: Primary serine deficiency disorders have a broad range of phenotypic spectrum. As an inborn error of metabolism, individuals with severe phenotype may be easily recognized as Neu-Laxova syndrome. However, late-onset mild phenotypes may be underdiagnosed and will lead to disastrous consequences due to treatment delays. Materials and Methods: Clinical features of patients with serine deficiency disorders were summarized in two unrelated patients. Skin and sural nerve biopsies were conducted in the patients. Whole exome sequencing (WES) was performed in the index patients. Sanger sequencing was used to analyze family co-segregation. Results: Patient 1 was a 19-year-old male presenting with infancy-onset ichthyosis and juvenile-onset neuropathy. Patient 2 was 17-year-old male manifesting childhood-onset ichthyosis and juvenile-onset neuropathy. Except for nystagmus, no other developmental or neurodegenerative disorders were found in the patients. Electrophysiological studies indicated a severe sensorimotor axonal neuropathy with a possible demyelinating component. High-dose oral L-serine and glycine completely alleviated skin lesions and only slightly improved neuropathy symptoms. Skin biopsies showed typical features consistent with ichthyosis and severe loss of unmyelinated axons. Sural biopsies revealed a severe loss of axons and a few thinly myelinated fibers. WES found a same homozygous variant c.43G>C (p.A15P) in the PSAT1 gene, which was co-segregated in the two families. Conclusions: Skin and nervous system may be the main affected targets in serine deficiency disorders. Our patients show a more simple and mild phenotype of PSAT1-related serine deficiency disorder. The pathological changes and regenerative ability of skin and peripheral nerves determine their response to serine supplement.